Study of the Dilatancy/Contraction Mechanism of Landslide Fluidization Behavior Using an Initially Saturated Granular Column Collapse Simulation. Issue 10 (28th September 2021) - Liang, Heng; He, Siming; Jiang, Yuanjun
Abstract: Fluidlike and integral sliding behaviors can be partly attributed to the dilatancy/contraction behavior of granular materials. A three‐dimensional two‐phase model and smoothed particle hydrodynamics method are applied to study the fluidization behavior by simulating the collapse of an initially fully saturated granular column. The dimensionless numbers (the initial aspect ratio, initial solid volume fraction, and Stokes number associated with the grain size) are varied to examine the collapse process and deposition characteristics. The profiles and front location during collapse highlight that the mechanism changes with the Stokes number and initial solid volume. The granular migration and pore pressure evolution characteristics are presented to clarify the differences in the collapse procedures and mechanisms pertaining to the simulation cases. The dimensionless final runout length and deposition height present monotonically increase and decrease following power laws with increasing initial aspect ratio, respectively; the dimensionless final runout length and deposition height also have monotonically decreasing and increasing relationships with increasing initial solid volume fraction and strongly increasing and decreasing characteristics during the transfer from the viscous flow regime to the inertial flow regime with increasing Stokes number, respectively. The simulation results indicate that the dynamic mechanism of the fluidization transformation is controlled by the Stokes number and initial solid volume fraction. Moreover, the coupling effect of the Stokes number, initial solid volume fraction and initial aspect ratio controls the collapse process of the initially saturated granular column. Key Points: Numerical simulations were performed on the collapse of an initially saturated granular column Influences of initial solid volume fraction, aspect ratio and Stokes number on the collapse dynamics and associated deposits were clarified The differences in the results could be attributed to the dilatancy/contraction mechanism and related pore liquid pressure